The Effect of Sinbiotic Supplement as Replacement for Antibiotic Growth Promoter on Growth and Size of Intestinal Villi in Broiler Chicken - Muhammad Arifin; Vembriarto Jati Pramono (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2014)
Over the past few decades, antibiotics have been used as growth promoters in poultry diet to improve animal performance and to obtain economic benefits. The aim of this study was to know the effect of sinbiotic derived from Bacillus subtilis as probiotic and Saccharomyces cerevisiae cell wall combination as one of antibiotic growth promoters (AGP) in broilers. Group 1 (control), group 2 (AGP), and group 3 (sinbiotic). Broilers from each group were necropsied for histological preparation and the length and width of intestinal villus were measured histologically. The data were taken from feed, body weight, Feed Conversion Ratio (FCR), and the length and width of intestinal villi. Analysis of Variance were used to analize the data. The results of the length and width of the duodenum, jejunum, and colon villi in group 3 and group 1 were showed significant differences (P <0.05) as well as a comparison between group 3 and group 2. Statistical analysis of weight gain during 5 weeks was showed significant differences (P <0.05) between groups except at week 2 and 3. Analysis of FCR was showed that there were significant differences (P <0.05) between groups on a weekly basis. It was concluded that sinbiotic increase the length and width of intestinal villi, increase the body weight gain ofchicken, and reduce the value of FCR, therefore sinbiotic can be used as an alternative replacement for Antibiotic Growth Promoter (AGP).